STUDI TENTANG LOYALITAS KONSUMEN KOPI KAPAL API DI KABUPATEN BONDOWOSO - Yudha Praja (Growth, 2021)
The purpose of this study was to determine directly or indirectly the effect of experiential marketing and brand image on consumer loyalty through consumer satisfaction of Kapal Api coffee in Bondowoso Regency. The number of samples in this study was 354. The analytical technique used was the Structural Equation Model (SEM) using WarpPLS 5.0. The results of data analysis show that (1) Experiential marketing variables have a significant effect on consumer satisfaction. (2) Brand image has a significant effect on consumer satisfaction. (3) Experiential marketing has a significant effect on consumer loyalty. (4) Brand image has a significant effect on consumer loyalty. (5) Consumer satisfaction has a significant effect on consumer loyalty. (6) Indirectly Experiential marketing has a significant effect on consumer loyalty through customer satisfaction. (7) Indirectly brand image has a significant effect on consumer consumer loyalty through consumer satisfaction.